2004
DOI: 10.4049/jimmunol.172.6.3635
|View full text |Cite
|
Sign up to set email alerts
|

The β2-Microglobulin Locus of Rainbow Trout (Oncorhynchus mykiss) Contains Three Polymorphic Genes

Abstract: β2-microglobulin (β2m) associates with MHC and related class I H chains to form cell surface glycoproteins that mediate a variety of functions in defense. In humans, monomorphism of a single β2m gene contrasts with the diversity and polymorphism of the class I H chain genes, and a similar picture was seen in almost all other species examined. In this regard, rainbow trout (Oncorhynchus mykiss) appeared unusual: trout β2m genes gave a complicated and polymorphic pattern in Southern blots, and a minimum of 10 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…Alignments revealed a high degree of sequence similarity between the three sequences obtained (99.6%). Higher-vertebrate β 2 m has no isoforms and is not polymorphic, but polymorphisms between different alleles have been found in some fish species (Shum et al, 1996;Magor et al, 2004;Xu et al, 2010b). In this study, three alleles were found in the miiuy croaker, which provides further evidence that confirms the above phenomenon.…”
Section: Sequence Diversity Analysissupporting
confidence: 81%
See 1 more Smart Citation
“…Alignments revealed a high degree of sequence similarity between the three sequences obtained (99.6%). Higher-vertebrate β 2 m has no isoforms and is not polymorphic, but polymorphisms between different alleles have been found in some fish species (Shum et al, 1996;Magor et al, 2004;Xu et al, 2010b). In this study, three alleles were found in the miiuy croaker, which provides further evidence that confirms the above phenomenon.…”
Section: Sequence Diversity Analysissupporting
confidence: 81%
“…In general, the β 2 m gene contains four exons and three introns in higher vertebrates, and consists of three exons and two introns in teleosts (Parnes and Seidman, 1982;Gussow et al, 1987;Lundqvist et al, 1999;Xu et al, 2010a); however, two distinct types of β 2 m have been identified in the red sea bream (Pagrus major) and the yellowtail (Seriola quinqueradiata) using expressed sequence tags (ESTs) (Kondo et al, 2010). β 2 m has no isoforms and is not polymorphic in higher vertebrates, but polymorphisms between different alleles have been found in some fish species (Shum et al, 1996;Magor et al, 2004;Xu et al, 2010b). The miiuy croaker (Miichthys miiuy) is an important economic marine fish in China, and the MHC class Iα and class II genes in this species has already been described (Xu et al, 2010c(Xu et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, class I genes and their genomic organizations have been analyzed in sharks (18), and in zebrafish, rainbow trout, Atlantic salmon, fugu and grass carp (19). These studies revealed that the class I amino acid sequences of fish and mammals share ,50% similarity and that many bony fish have MHC features distinct from those typical in mammals, like nonlinkage of class I and class II genes, extreme levels of MHC class I polymorphism, and multiple b2m loci (20). Moreover, similar to findings in humans, CD2, CD3, CD4, CD8a/b, and TCRa/b homologs have also been identified in bony fishes (21), suggesting that p/MHC I-based CD8 + T cell-mediated immunity might be present in fish species.…”
mentioning
confidence: 99%
“…The genomic structure of these genes contains four exons and three introns. The ␤2m genes are genetically unlinked and are located outside of the MHC region (9).…”
mentioning
confidence: 99%